The Transfer of Sub-District Health Promoting Hospitals to Local Government Organizations: Progress and Challenges - Uansri, Sonvanee; Markchang, Kamolphat; Chotchoungchatchai, Somtanuek; Ontong, Sasivimol; Panapong, Nitjanan; Pattanasiri, Thanin (Journal of Health Systems Research, 2024)
This qualitative research reviewed documents to investigate the progress of health facility decentralization according to sequential plans, decrees following revisions of the Decentralization Plan Act. Specifically, this research examined the criteria and procedures of transferring the Chaloem Phra Kiat 60 Years Nawamintrachini Health Centers and sub-district health promoting hospitals to local government organizations in 2021. The results reveal continuous improvements in the clarity and flexibility of the transfer criteria and conditions. Notably, the transfer criteria have been segmented into stages to evaluate the readiness and potential of local government organizations for the expected responsibilities. However, significant challenges persist, particularly regarding the laws and regulations governing the operations of medical and health professionals, including all other categories of human resources, and budgetary management by the National Health Security Office related to primary health care function of the transferred facilities. These challenges were compounded by a lack of continuity in decentralization and operational plans, budgetary constraints, legal issues encountered in the transfer of human resources, and an unclear division of duties between related units. The study offers policy proposals as follows: 1) review and amend the Ministry of Interior’s regulations regarding the operations of transferred health facilities to enhance efficient management and service delivery. 2) Amend regulations to increase workforce flexibility of transferred health facilities to local government organizations taking account of local contexts, issues, and limitations within the personnel budget framework. 3) Allocate budgets according to the responsibilities of transferred health facilities to ensure stable income to attain self-managed revenues for effective health service delivery.